Textiles and the skin - Elsner, Peter 1955-; Hatch, Kathryn; Wigger-Alberti, Walter 1964- (Current problems in dermatology, 2003)
Completely new textile technologies have recently been developed with the goal of giving additional functionality to garments. Textiles have been improved to protect against UV radiation and toxic gases or to enhance breathability. In addition, they may have integrated sensors to diagnose medical conditions or may be equipped with carrier molecules to absorb substances from the skin and release therapeutic compounds. At the same time, the awareness of unwanted effects clothing may have on human health has increased. This volume familiarizes the dermatologist, allergologist and occupational physician with what he should know about textiles, and, on the other hand, the textile or chemical engineer with what he should know about the human skin. Further, it is divided into two parts the first of which discusses the functionality of textiles also in medicine, for instance in the prevention of skin infections or wound healing. The last part deals with allergic contact and irritant dermatitis and the risks of possible exposure to hazardous chemical residues in textiles. For the first time the knowledge of textile engineers and dermatologists has been brought together to stimulate a promising interchange